BACTERIAL LYSATES MIXTURE FOR THE TOPICAL ADMINISTRATION IN PROPHYLAXIS AND TREATMENT OF CHRONIC TONSILLITIS IN CHILDREN - T.I. Garashchenko; V.G. Volodarskaya ("Paediatrician" Publishers LLC, 2009)
Chronic tonsillitis is the infectious and allergic disease; the main clinical symptom of this disease is chronic inflammation of palatine tonsils. The prevalence of chronic tonsillitis is up to 10% among adults and 15% - among children. Undoubtedly, the prevention of exacerbations of chronic tonsillitis is difficult task. Its significant component is immunocorrection with elements of vaccinal process, because tonsils themselves are the part of forming immune system of a child. Imudon can be recommended for the inclusion to the yearly prophylactic treatment courses in patients with chronic tonsillitis, hypertrophy of palatine tonsils and recurrent tonsillopharyngitis. Key words: children, chronic tonsillitis, prophylaxis, treatment, bacterial lysates mixture. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):109-112)